A new multidimensional group intervention for cognitive and psychosocial functioning for older adults: Background, content, and process evaluation - Chadjikyprianou, Andreas; Constantinidou, Fofi (Frontiers in Medicine, 2023)
Introduction An essential element of quality aging is the maintenance of cognitive and psychosocial functioning. The principal objective of the present paper was to present the theoretical framework, content and process evaluation of a newly developed multi-dimensional group intervention designed to strengthen/improve areas of cognitive and psychosocial functioning in adults over 65. Methods The intervention implements multiple methodologies aiming to facilitate contextual integration of learned concepts and strategies derived from clinical psychology and rehabilitation. It moves seamlessly on the cognition–emotion axes and consists of five active ingredients selected to address challenges associated with aging: Memory Compensatory Strategies, Problem-Solving, Emotion Regulation, Mindfulness, and Locus of Control. Thirty participants joined the intervention group aged 65–75 years (M = 69.03; SD = 3.04). All 30 participants who were included in the intervention group completed the program. Results Results from the Participant Satisfaction Scale indicate that the program was perceived very positively by participants, who also reported implementing their newly learned strategies in activities of daily life. Furthermore, there was high correlation between internal locus of control and the learned strategies. Discussion The outcomes of this analysis indicate that the intervention is feasible and well tolerated by our target group. This multidimensional intervention may offer a valuable contribution to public health care and dementia prevention for older adults. Clinical Trial Registration [https://clinicaltrials.gov/ct2/results?cond=NCT01481246], identifier [NCT01481246].